OPERATIONS MANAGEMENT : Sustainability and Supply Chain Management - Heizer, Jay; Render, Barry; Munson, Chuck (Charles Lee) (Pearson, 2023)
"The goal of this text and its accompanying online resources is to present students a broad introduction to the field of operations in a realistic, practical, and applied manner. We want students to understand how operations work within an organization by seeing first-hand what goes on behind the scenes at a concert or major sports event, placing an order through Amazon.com, boarding a flight on Alaska Airlines, or taking a cruise with Celebrity Cruises. This text along with its online learning tools and resources offers behind-the-scenes views that no other product on the market provides and one that students tell us they value because they gain a true understanding of operations"--